Treading Water: Tools to Help US Coastal Communities Plan for Sea Level Rise Impacts - Smith, Emily A.; Sweet, William; Mitchell, Molly; Domingues, Ricardo; Weaver, Christopher P.; Baringer, Molly; Goni, Gustavo; Haines, John; Loftis, J. Derek; Boon, John; Malmquist, David (Frontiers in Marine Science, 2019)
As communities grapple with rising seas and more frequent flooding events, they need improved projections of future rise and flooding over multiple time horizons to assist in a multitude of planning efforts. There are currently a few different tools available that communities can use to plan including the Sea Level Report Card and products generated by a U.S. Federal interagency task force on sea level rise. These tools are a start, but it is recognized that they are not necessarily enough at present to give communities the types of information needed for decision support, which ranges from seasonal to decadal in nature, generally over relatively small geographic regions.